Workshop of the painter Gottfried Ezekiel – the technique of 18th-century decorations in Bodø (Norway) - Klaudia Rajmann (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The presented research was focused on a group of Norwegian decorative paintings from  about 1750, executed by Gottfried Ezekiel – the painter of Prussian origin, formed in Königsberg. The aim of described project was to compare the style and the technique of works in Bodin church and of the so called Louis-Philippe Room – lading to determine the characteristics features for the artist’s workshop.